2018
DOI: 10.1364/boe.9.006519
|View full text |Cite
|
Sign up to set email alerts
|

Complementary use of polarization-sensitive and standard OCT metrics for enhanced intraoperative differentiation of breast cancer

Abstract: We report the development and implementation of an intraoperative polarizationsensitive optical coherence tomography (PS-OCT) system for enhancing breast cancer detection. A total of 3440 PS-OCT images were intraoperatively acquired from 9 human breast specimens diagnosed by H&E histology as healthy fibro-adipose tissue (n = 2), healthy stroma (n = 2), or invasive ductal carcinoma (IDC, n = 5). A standard OCT-based metric (coefficient of variation (CV)) and PS-OCT-based metrics sensitive to biological tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…The measurement bias between the en-face birefringence map and histology is only 185 ± 121 µm in our study. Although we cannot claim that the en-face birefringence map can predict tumor margin accurately in this study, this result still inspires the potential use of PS-OCT to define tumor margins in the future, as has been done in studies of breast cancer [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 74%
“…The measurement bias between the en-face birefringence map and histology is only 185 ± 121 µm in our study. Although we cannot claim that the en-face birefringence map can predict tumor margin accurately in this study, this result still inspires the potential use of PS-OCT to define tumor margins in the future, as has been done in studies of breast cancer [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 74%
“…With various polarization-based technologies developed to probe structural and functional information of tissues, such as polarization-sensitive optical coherence tomography and Mueller polarimetric imaging, the latter has emerged as a prospective tool in diagnostic applications. 1,2 Studies have shown that optical polarization enhances the optical contrast required for effective differentiation. Further integration with existing optical instruments such as the endoscope makes polarimetric imaging suitable for in vivo applications.…”
Section: Introductionmentioning
confidence: 99%
“…Polarization-sensitive OCT (PS-OCT) 1 has become an exceptionally useful imaging technique that complements the scattering intensity contrast in standard OCT systems and provides additional diagnostic information and guidance 2 7 . By analyzing the polarizations of the scattered light, PS-OCT imaging systems measure the birefringence within the imaged tissue sites, which is largely related to the orientation and organization of tissue structures.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the additional polarization information provided by PS-OCT facilitates the visualization of unrecognizable features in OCT images 4 , 9 , 10 . In particular, PS-OCT has been used in clinical applications 2 , 6 8 to effectively differentiate cancer tissue and connective tissue based on their different birefringence, while these types of tissues appear very similar in standard OCT images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation